2014
DOI: 10.1016/j.foodres.2014.05.079
|View full text |Cite
|
Sign up to set email alerts
|

Production, characterization and foamability of α-lactalbumin/glycomacropeptide supramolecular structures

Abstract: The study of protein interactions has generated great interest in the food industry. Therefore, research on new supramolecular structures shows promise. Supramolecular structures of the whey proteins α-lactalbumin and glycomacropeptide were produced under varying heat treatments (25 to 75°C) and acidic conditions (pH3.5 to 6.5). Isothermal titration calorimetry experiments showed protein interactions and demonstrated that this is an enthalpically driven process. Supramolecular protein structures in aqueous sol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 38 publications
3
7
0
Order By: Relevance
“…Our current results suggest that at pH 3.0, high NaCl levels (0.75 and 1.0 M) led to increased protein‐protein repulsion within the helix structure, which led to higher levels of the unordered structures. The results also agree with the work of Diniz et al () who showed higher secondary structure formation at acidic pH values.…”
Section: Resultssupporting
confidence: 93%
“…Our current results suggest that at pH 3.0, high NaCl levels (0.75 and 1.0 M) led to increased protein‐protein repulsion within the helix structure, which led to higher levels of the unordered structures. The results also agree with the work of Diniz et al () who showed higher secondary structure formation at acidic pH values.…”
Section: Resultssupporting
confidence: 93%
“…Foam capacity was determined as described by Ivanova et al [14] and Diniz et al [15] with some modification. Foam capacity (FC) was determined by volume increase (%) immediately after whipping and was calculated by the formula: ,…”
Section: Evaluation Of Foam Capacitymentioning
confidence: 99%
“…By using such technology, The Iceland Company "BIOEFFECT" has applied for the first time a plant-based transgenic platform for large-scale production of Epidermal Growth Factors (EGF) for cosmetic use, expressed in genetically engineered barley seeds. However, even that The emulsifying activity index (EAI) and emulsion stability index (ESI) were determined according to [48]. However, the recent interests in molecular farming have been focused on adaptation of plant cell culture technology for the production of recombinant proteins.…”
Section: Molecular Farming For Production Of Recombinant Proteinsmentioning
confidence: 99%
“…Recently, the Korean company "Natural Bio-Materials (NBM)", has launched series of active cosmetic ingredients containing growth factors (Epidermal Growth Factor, Basic Fibroblast Growth Factor, Insulin-like Growth Factor-1, Keratinocyte Growth Factor, Fibroblast Growth Factor-7, and Vascular Endothelial Growth Factor), expressed by recombinant rice (Oryza sativa L.) cell cultures (Table 1). However, even that The emulsifying activity index (EAI) and emulsion stability index (ESI) were determined according to [48]. Model emulsion systems were prepared by mixing polysaccharides, water and sunflower oil for 5 min at 10 000 rpm by homogenizer (Ultra Turrax IKA T18 Basic, Germany).…”
Section: Molecular Farming For Production Of Recombinant Proteinsmentioning
confidence: 99%